The Role of Financial Literacy in Enhancing MSME Performance in Emerging Economies - Aryo Prakoso; Fauziyah Azzahro; Senato Erasandi (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study explores the critical role of financial literacy as a strategic determinant of the performance of Micro, Small, and Medium Enterprises (MSMEs) in East Java, one of Indonesia’s largest regional economies. This research seeks to bridge the theoretical gap between individual and organizational human capital by empirically examining the direct influence of owner-managers’ financial competence on business success amid widespread digital transformation. Hypothesis testing employed a quantitative methodology. Data collected from MSMEs in East Java in 2025 were analyzed using covariance-based Structural Equation Modeling (SEM). The robustness of the measurement instrument was confirmed through Confirmatory Factor Analysis (CFA), and the validity of the structural model was rigorously assessed against established goodness-of-fit criteria to examine the proposed causal pathways. The findings provide empirical support for the view that financial literacy emerges as a significant and positive predictor of enhanced MSME performance. The model demonstrated superior fit, thereby affirming the validity of the theoretical framework. This study offers a theoretical contribution by successfully contextualizing the Resource-Based View within the micro-enterprise domain, articulating financial literacy as a critical intangible asset that drives competitive advantage. For practitioners and policymakers, these findings provide authoritative evidence to support integrated intervention strategies that synergize financial education, thereby fostering a more resilient, productive, and sustainable MSME sector essential for inclusive economic growth.